Economic valuation of mangrove ecosystem in Tana Tidung Regency - Mazlan, Mazlan; Yulianda, Fredinan; Yulianto, Gatot; Rachmawani, Dori (Acta Aquatica: Aquatic Sciences Journal, 2024)
Mangrove ecosystems are found in the area where land meets the sea. Potential of mangrove ecosystem are abundant because of their significant ecological and economic role, mangroves are known as multifunctional ecosystems. Ponds and the associated biota are two examples of the direct and indirect benefits of mangrove ecosystems. The research aim is to calculate the potential benefits of mangrove ecosystems in Tanah Tidung Regency. The method used for calculation of the value of resource benefits using the total economic value approach. The results showed that the Potential Use Value of mangrove ecosystems in Tana Tidung Regency reached Rp 305.529.644.089 per/year. So, it can be ascertained that mangroves have great potential in improving the welfare of people who can utilize them.Keywords: Economic Value; Mangrove; Tana Tidung